Role of subcutaneous suction drain in reducing surgical site infection in emergency laparotomy - Naik, Arun K.; S. V., Arya; Sharma, Ashok K. (International Surgery Journal, 2022)
Background: Surgical site infection (SSI) is a major postoperative wound complications associated with open abdominal surgery and is related to increased morbidity, mortality and healthcare costs. A subcutaneous suction drain reduces the dead space in the subcutaneous tissue plane and thereby prevents accumulation of fluid and seroma formation. In this study we observed the role of subcutaneous drain in reducing SSI in emergency laparotomies. Methods: Prospective randomized comparative study comprising of 108 patients on the basis of inclusion and exclusion criteria. 54 patients were called cases in whom subcutaneous suction drain was placed and 54 patients were called controls in whom no drain was placed. Antibiotic prophylaxis was given to all patients. Surgical site infection (SSI) was diagnosed and graded using Southampton wound grading system. Results: 24% of cases and 46% of controls developed SSI, 9% of cases and 33% of controls developed wound dehiscence and mean duration of hospital stay was 6days in cases and 10days in controls. All above parameters were statistically significant with p<0.05. Conclusions: Subcutaneous suction drain is effective in reducing surgical site infection (SSI), wound dehiscence and mean duration hospital stay in emergency laparotomies.